Warriors of God : Richard the Lionheart and Saladin in the Third Crusade - Reston, James (New York Doubleday, 2001)
The epic story of the battle for the Holy Land explores the conflict that transformed the world during the late twelfth century and the roles of Richard the Lionhearted, the English king, and Saladin, the visionary Islamic leader.
Includes bibliographical references (p. 347-354) and index.
Keywords: Richard -- I, -- King of England, -- 1157-1199.; Saladin, -- Sultan of Egypt and Syria, -- 1137-1193.; Crusades